Use of Blenderized Tube Feeding in Adult and Pediatric Home Enteral Nutrition Patients. (April 2017) - Epp, Lisa; Lammert, Lisa; Vallumsetla, Nishanth; Hurt, Ryan T.; Mundi, Manpreet S.
Background: Long-term use of enteral nutrition (EN) continues to increase due to significant noted benefits. Patients also continue to express significant desire to pursue holistic and organic diets. Despite this, many nutrition providers are not well versed in assisting patients with blenderized tube feeding (BTF), and prevalence of its use is unknown. Methods: A validated survey was administered to Oley Foundation members or individuals with access to the Oley website to assess the prevalence of BTF. Results: A total of 216 participants took the survey, of whom 125 (57.8%) were pediatric patients with a mean age of 5.4 ± 3.5 years and 91 (42.2%) were adults with a mean age of 51.7 ± 19.5 years. Of pediatric patients, 112 (89.6%) used BTF for an average of 71% of their total daily nutrition intake; 93 (83%) reported that BTF comprised >50% of their daily EN, 12 (10.7%) reported it comprised 25%–50% of their daily enteral intake, and 7 (6.3%) reported BTF comprised < 25% of their daily intake. In the adult population, 60 (65.9%) used BTF for an average of 56% of total daily nutrition intake; 41 (68.4%) reported BTF comprised >50% of their daily nutrition intake, 11 (18.3%) reported it compromised 25%–50%, and 8 (13.3%) reported BTF comprised <25% of their daily intake. Conclusions: Most of the pediatric and adult patients surveyed use BTF as some portion of their enteral intake, making it essential that clinicians expand their knowledge related to BTF to appropriately care for this patient population.